Public Service Motivation Model in Rural and Urban Land and Building Tax Services At Badan Pendapatan Daerah Banyuasin Regency : Case Study of Talang Kelapa District) - Rahmawati, Rahmawati; Alfitri; Slamet Widodo; Raniasa Putra (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2024)
This research is motivated by the low interest of the people in the Talang Kelapa sub-district and Tanjung Lago sub-district in paying land and building taxes in rural and urban areas. This study aims to determine the implementation of land and building tax payments in rural and urban areas, public service motivational practices and tax service models in Banyuasin Regency. The method used is observation and interviews with tourists and the surrounding community as well as using literature studies. From the results of the study it can be seen that the payment of rural and urban land and building taxes in Banyuasin Regency in 2022 has not reached the target and still leaves tax bills that have not been paid by the community. The motivation for services provided by tax officers both at the Regional Revenue Agency and by village heads, village heads is still not optimal because people are still hesitant to make payments. rural and urban buildings are still low as well as the motivation for services provided by officers is still not optimal.